Plankton seasonality and its relationship with some physicochemical factors in south-eastern coasts of Bay of Bengal, Bangladesh (Dhaka University Journal of Biological Sciences, 2023)
This study was conducted between January and December, 2014 in four sampling stations of the Bay of Bengal, namely Teknaf beach, Inani beach, St. Martin’s Island and Sonadia Island. A total of 39 plankton species were recorded from 4 stations. Among those, 8, 3,2,14 and 2 species belonged to algae, protozoa, rotifera, copepods, and ostracods respectively. Copepoda was the most abundant zooplankton at all stations. The highest monthly density of plankton was 111.2 ind./l at Teknaf beach and the lowest was 5.6 ind./l at Sonadia Island of the Bay of Bengal. Some species such as, Biddulphia sp., Coscinodiscus centralis, copepod nauplii, Canthocalanus pauper, Acrocalanus spp., Clausocalanus spp., Oithona spinirostris were more abundant than other plankton. The plankton population showed positive correlation with physicochemical factors like water temperature and air temperature whereas negatively correlated with pH, DO, CO2, salinity, acidity and alkalinity with a few exceptions.Dhaka Univ. J. Biol. Sci. 32(2): 135-148, 2023 (July)